Dynamic Low-Latency Load Balancing Model to Improve Quality of Experience in a Hybrid Fog and Edge Architecture for Massively Multiplayer Online (MMO) Games - Ernesto José García Fernández de Castro; Ernesto José García Puche; Daladier Jabba Molinares (Applied Sciences)
In the evolving landscape of online gaming, ensuring a high quality of experience (QoE) for players is paramount. This study introduces a dynamic, low-latency load balancing model designed to enhance QoE in massively multiplayer online (MMO) games through a hybrid fog and edge computing architecture. The model addresses the challenges of latency and load distribution by leveraging fog and edge resources to optimize player engagement and response times. The experiments conducted in this study were simulations, providing a controlled environment to evaluate the proposed model’s performance. Key findings demonstrate a significant 67.5% reduction in average latency, a 60.3% reduction in peak latency, and a 65.8% reduction in latency variability, ensuring a more consistent and immersive gaming experience. Additionally, the proposed model was benchmarked against a base model, based on the article titled “A Cloud Gaming Architecture Leveraging Fog for Dynamic Load Balancing in Cluster-Based MMOs”, highlighting its superior performance in load distribution and latency reduction. This research provides a framework for future developments in cloud-based gaming infrastructure, emphasizing the importance of innovative load balancing techniques in maintaining seamless gameplay and scalable systems.